Associação entre determinantes sociais de saúde e provável bruxismo em escolares: estudo transversal - Quadros, Letícia Angonesi (2024)
Objective: To evaluate the association between social determinants of health and probable sleep and wake bruxism in schoolchildren. Methods: A cross-sectional study was designed in which schoolchildren aged 8 to 12 years were evaluated. Bruxism assessment involved a clinical examination and the application of the structured questionnaire which generated a bruxism score. Social determinants of health, such as sex, age, skin color, family income, caffeine consumption, physical activity, stress, and significant life changes, were measured through a structured questionnaire and open-ended questions administered to parents or guardians. Unadjusted and adjusted Poisson regression analyses were used to assess the association of predictor variables (social determinants of health) with probable bruxism. Results: Twenty-seven schoolchildren were evaluated. In the unadjusted analysis, male patients and those with a family income of less than one minimum wage had higher overall bruxism scores (p<0.01). Patients who were stressed, consumed high amounts of caffeine, and did not regularly participate in sports also had higher overall bruxism scores (p<0.01). In the adjusted analysis, stressed patients had 2.54 times higher bruxism scores (RR 2.54; 95% CI 1.38-4.68), individuals from families earning less than one minimum wage had higher bruxism scores (RR 2.47; 95% CI 1.41-4.32), and male individuals had 2.01 times higher bruxism scores compared to female schoolchildren (RR 2.01; 95% CI 1.05-3.82). Conclusion: Schoolchildren with a family income of less than one minimum wage, who were stressed, and who were male had higher scores of bruxism.